1996
DOI: 10.1074/jbc.271.44.27201
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Death Induced by Tumor Necrosis Factor-α Is Inhibited by the Bcl-2 Family Member, A1

Abstract: Endothelial cells play a central role in the inflammatory process. Tumor necrosis factor-␣ (TNF) is a multifunctional cytokine which elicits many of the inflammatory responses of endothelial cells. While TNF directly causes apoptosis of tumor cells and virally infected cells, normal cells are generally resistant. However, most resistant cells, including human endothelial cells, can be rendered susceptible to TNF by inhibiting RNA or protein synthesis. This finding suggests that TNF provides a cell survival sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
213
2
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(228 citation statements)
references
References 47 publications
12
213
2
1
Order By: Relevance
“…A similar phenomenon has been described for TNF (6). While exposure to TNF does not cause endothelial apoptosis, the combination of TNF and CHX or actinomycin D does (6). In both cases, the concomitant induction of antiapoptotic genes has been shown to inhibit the apoptotic pathway that is activated (4,6).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…A similar phenomenon has been described for TNF (6). While exposure to TNF does not cause endothelial apoptosis, the combination of TNF and CHX or actinomycin D does (6). In both cases, the concomitant induction of antiapoptotic genes has been shown to inhibit the apoptotic pathway that is activated (4,6).…”
mentioning
confidence: 78%
“…In contrast, when the expression of new genes is inhibited using cycloheximide (CHX) 3 or actinomycin D, endothelial cells become sensitized to the apoptotic signals evoked by LPS (3)(4)(5). A similar phenomenon has been described for TNF (6). While exposure to TNF does not cause endothelial apoptosis, the combination of TNF and CHX or actinomycin D does (6).…”
mentioning
confidence: 86%
“…18,26,[27][28][29] However, its protective activity is not always absolute, as Bfl-1/A1 is less protective than Bcl-xL in microvascular endothelial cells treated with tumor necrosis factor (TNF)a and only delays TNFa-induced apoptosis in HT1080 fibrosarcoma cells. 25,30 Similarly, while Bfl-1 potently blocks etoposideinduced cell death in HT1080 fibrosarcoma cells, it is much less effective against this agent in Jurkat T-cells. 25,28 These results suggest that the level of protection conferred by Bfl-1 is perhaps subject to modulation in different cell contexts and in response to particular apoptotic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Bcl2a1 has protective effects in some experimental paradigms but promotes programmed cell death in others. 11 Furthermore, it responds to oxidative stress, is a direct transcriptional target of nuclear factor (NF)-kB 12,13 and is induced by the inflammatory cytokines tumour necrosis factor (TNF-a) and interleukin (IL)-1b 14,15 These unique characteristics of Bcl2a1 prompted us to study the role of this protein in ALS, as reactive oxygen species, NF-kB, TNF-a and IL-1b have been proposed by us and by others to contribute in the molecular crosstalk occurring among different cell types in the pathogenesis of ALS 1,6 We have investigated expression of the Bcl2 family members in spinal cords of transgenic G93A-SOD1, WT-SOD1 and non-transgenic mice. As shown in Figure 1, Bcl2a1 is the only member of this family to be upregulated in both asymptomatic and symptomatic G93A mice (Figure 1a), with a tendency to decrease in the final stages of disease.…”
mentioning
confidence: 99%
“…It has been shown that Bcl2a1 has various effects in response to TNF-a in different cell cultures: it acts as an antiapoptotic in immune-derived cell lines, 13 in microvascular endothelial cells 20 and in HT1080 fibrosarcoma cells, 14 whereas it is clearly proapoptotic in B cells. 11 In this work, we demonstrate in different cell cultures (NSC-34, undifferentiated and differentiated ETNA cells and primary cultures from spinal cords) that the overexpression of Bcl2a1 and G93A-SOD1 increases the level of cell death after exposure to TNF-a, a situation mimicking the condition of neuroinflammation occurring in ALS.…”
mentioning
confidence: 99%